Soft switching modulation strategy based on bipolar (PSM) with improved efficiency in high-frequency link inverters - Ali, Asif; Su, Jianhui; Yang, Gang; Ali, Amjad; Hameed Shaikh, Pervez (Frontiers in Energy Research, 2023)
High Frequency-Link (HFL) Inverters have been employed to integrate renewable energy sources into utility grids and electric vehicles. The soft-switching range of High-Frequency Link Inverters (HFLI) is increased using auxiliary inductors and capacitors. The application of auxiliary components increases the conduction loss and the complexity of the circuit. The literature indicates that the existing soft-switching methods suffer from higher duty cycle loss, voltage spikes, and lower efficiency owing to the resonance between the parasitic capacitance of switches and the leakage inductance of the transformer. Therefore, it is imperative to develop a modulation strategy that can improve the efficiency of HFLI. In this context, the proposed study develops a cycloconverter-type High-Frequency Link Inverter (CHFLI) based on a Bipolar Phase Shift Modulation (BPSM) strategy without the use of auxiliary components. The proposed modulation strategy enables the semiconductor switches to operate under zero voltage switching. The full-bridge inverter and Full Bridge Active Clamper Circuit (FBAC) switches operate at the same gating signals with a constant duty cycle of 50%. The proposed topology uses built-in magnetizing inductance to achieve zero voltage switching and reduce the duty cycle loss. The leakage energy is recycled from the output filter inductor to the load side using the FBAC. The results indicate that the proposed modulation strategy achieves ZVS and simultaneously achieves an efficiency of 95%. The proposed modulation strategy is easy to implement and does not require complex circuitry.